The Hermeneutic of Concealing and Un-concealing of Being in Madhyamaka-Buddhism and Advaita-Ved?nta (Global Journal of Human-Social Science, 2017)
In the history of Indian philosophy the relationship between Advaita-Ved nta and Madhyamaka-Buddhism is constantly disputed It is argued how one thought has eventually benefited from the other This work explores the above-mentioned relationship in the context of Heidegger s intercession with Nietzsche where concealment and un-concealment are understood as explicit ontological characters of Being Subsequently N g rjuna s description of reality as nya or void is explored as an expression of nihilism nevertheless similar to Heidegger s observation of concealment of Being in nihil And Advaita-Ved nta as a thinking of non-duality expresses the hermeneutic of un-concealment of Being i e of one and the same These ontological characters of Being allow us to discover a sabotaging brotherhood between N g rjuna and ankara because the nihil and something are ontologically two essential sides of the same thinking
Keywords: buddhism; advaita-ved?nta; being; intercultural ontology; heidegger; indian philosophy